2009
DOI: 10.1111/j.1538-7836.2009.03292.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of bioaccumulation of dalteparin at a prophylactic dose in patients with various degrees of impaired renal function

Abstract: To cite this article: Schmid P, Brodmann D, Fischer AG, Wuillemin WA. Study of bioaccumulation of dalteparin at a prophylactic dose in patients with various degrees of impaired renal function. J Thromb Haemost 2009; 7: 552-8.Summary. Background: Low-molecular-weight heparins (LMWH) have been shown to be effective and safe for prophylaxis of thromboembolic diseases. However, issues regarding safety and optimal use of LMWH arise in patients with renal insufficiency (RI). Objectives: To compare pharmacokinetic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
1
18
0
6
Order By: Relevance
“…Tincani showed that no bioaccumulation occurred after 6 days of dalteparin prophylaxis, irrespective of renal function without major bleeding events. 28 Studies performed by both Schmid et al and Shprecher et al showed no increase in anti-factor Xa level in patients with renal impairment in prophylactic or therapeutic dosing, 10,29 and a metaanalysis from 2006 notes that insufficient data exist to assess risk for major bleeding for other LMWHs such as dalteparin and tinzaparin, while still advising adjusted dose enoxaparin in CKD. 30 Strengths.…”
Section: Discussionmentioning
confidence: 99%
“…Tincani showed that no bioaccumulation occurred after 6 days of dalteparin prophylaxis, irrespective of renal function without major bleeding events. 28 Studies performed by both Schmid et al and Shprecher et al showed no increase in anti-factor Xa level in patients with renal impairment in prophylactic or therapeutic dosing, 10,29 and a metaanalysis from 2006 notes that insufficient data exist to assess risk for major bleeding for other LMWHs such as dalteparin and tinzaparin, while still advising adjusted dose enoxaparin in CKD. 30 Strengths.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between renal impairment and drug accumulation for the various LMWHs appears to be variable and may be related to the chain length distribution of the different LMWH preparations (54). Two recent studies in hospitalized patients, the majority of whom were critically ill and had creatinine clearances less than 30 mL/min, have shown no bioaccumulation of dalteparin 5000 U once daily based on serial anti-factor Xa levels (55,56). Therefore, we do not reduce the prophylaxis dose of dalteparin in patients with renal insufficiency.…”
Section: Anticoagulant Use In Renal Insufficiencymentioning
confidence: 99%
“…3,4 In patients with severe renal impairment (creatinine clearance 15-30 mL/min; stage IV chronic kidney disease), LMWH dose reduction and anti-Xa monitoring should be performed. 5 For patients with stage V chronic kidney disease, intravenous unfractionated heparin should be used for this purpose. After warfarin discontinuation, a daily therapeutic dose of LMWH is initiated once the INR falls below the therapeutic range.…”
Section: Systematic Approach To Anticoagulantsmentioning
confidence: 99%